Programa de formação em informática para professores no atendimento de alunos com deficiência visual - Ferreira, Naidson Clayr Santos (Universidade Federal de São Carlos, 2017)
In the past years, computing has progressed in such a way that it has reached many aspects of human life, producing modern elements that accelerate communication among people, institutions and their mutual relations. Among these, there is the school. The changes that happen day-by-day because of computer science may interfere in the educational process. The teacher needs to be prepared so that learning can happen in several ways and spaces. This way, a development on the teacher way of acting is required. Thus, this study was aimed to evaluate an IT training program for teachers who attend students with visual impairment. This research had the following specific objectives: a) to contribute to the teacher‟s appropriation of theoretical and practical knowledge about visual impairment; b) to provide training to teachers so they can operate the computer using basic functions of the main products such as operating systems (Windows, Linux), text editors (Word 2010), the spreadsheets (Excel 2010), presentation applications (PowerPoint), the Internet; c) to provide teachers with training in the use of softwares for the elaboration of accessible materials, screen amplifiers and screen readers, for attending students with visual impairment; d) to verify the performance of teachers in practical activities with students with visual impairment. e) to correlate the performance of teachers in the program with their performance in the practice with students with visual impairment. Twelve teachers took part of this study, distributed as follows: a substitute teacher belonging to the teaching staff of the Instituto Federal Baiano – Campus Guanambi, and 11 from the Municipal Education Network of Guanambi and Caetité who work in Multifunctional Resource Rooms. The data collection site was the Instituto Federal Baiano Federal – Campus Guanambi. For this purpose, the computer laboratory was used with 20 computers, equipped with the necessary software for the execution of the Computer Training Program. The instruments used for the data collection were: an initial questionnaire for checking profile and the level of knowledge in basic informatics, informatics in the school context and informatics in special education; in addition, before and after tests related to the Modules and activity practices. For the data analysis procedures, comparisons were made between the before and after test scores, the teachers‟ frequency in each module and their grades in the activity practices. The course was divided into nine modules: Module I - Basic Computer Skills, within 30 hours; Module II – Application Systems I, within 40 hours; Module III – Application Systems III within, 20 hours; Module IV – Didactic Material Accessibility, within 10 hours; Module V – Accessible Book, within 10 hours; Module VI – Easy Braille, within 20 hours; Module VII – Screen magnifiers, within 10 hours; Module VIII – Windows screen readers within 40 hours, and Module IX – Linux screen magnifier, within 20 hours. The course took place in two academic periods, that is, from October to December 2014, and after the teachers‟ vacations, from February to September 2015. The results showed that the research contributed to the teachers' learning process in order to operate the computer using the basic functions of the main products such as operating systems (Windows, Linux), text editors (Word 2010), the spreadsheets (Excel 2010), presentation applications (PowerPoint), the Internet. It also enabled the teachers to the use of softwares in the elaboration of accessible materials to attend visually impaired students, as well as the use of screen magnifiers and readers to assist students with visual impairment.
In computer formation program for teachers in the care of students with visual impairment.
Keywords: Educação Especial; Deficiência Visual; Formação Docente; Informática; Special education; Visual impairment; Teacher training; Computing; CIENCIAS HUMANAS::EDUCACAO